Pelaksanaan Layanan Informasi Bimbingan Konseling Guna Mencegah Stunting Pada Masyarakat - Ahmad Syarqawi; Mutiara Aulia; Sri Rezky; Nadila Nadila; Hafsah Dahni Rahmayani Dahni Rahmayani (Jurnal Bimbingan dan Konseling Indonesia, 2023)
Stunting is a chronic nutritional problem caused by a lack of nutritious food intake over a long period of time, a lack of clean water that causes diarrhea, a shortage of exclusive breastfeeding so that children's needs are not fully met, and many other factors that cause stunting. Individuals with short stature due to impaired growth in children under the age of five are referred to as stunting. However, many people do not know about stunting and the treatments that can be done to prevent it. This activity aims to increase the knowledge of the Karang Anyar village community about stunting, including the causes, prevention that can be done, and treatment that must be given to residents who experience it. Counseling and guidance play an important role in implementing information services to prevent stunting in the community in Karang Anyar village. The target of the research is the residents of Karang Anyar village. The method used in this study uses qualitative research methods with descriptive techniques. The results of this study are expected to provide information and knowledge so that they can change people's behavior to prevent stunting in Karang Anyar village.